More: How to do more with more in 2022 - Harriet E Watkins; Jacquelyn Cato (Academic Chairpersons Conference Proceedings, 2022)
In 2022 we are dealing with new academic realities. This presentation will investigate current faculty concerns and explore the ways academic coaches assist faculty and put the personal touch in online courses necessary to support and enhance the student experience. Providing the ability to scale and save on instructional costs.
Keywords: online; support; students; faculty; coaching